2020
DOI: 10.1002/ptr.6875
|View full text |Cite
|
Sign up to set email alerts
|

Artepillin C as an outstanding phenolic compound of Brazilian green propolis for disease treatment: A review on pharmacological aspects

Abstract: Propolis is a viscous resin consisting of plant material (shoots, flowers, and plant exudates), salivary secretions and waxes produced by Apis mellifera bees. Its popular use aroused the interests of scientific research, which proved to be a potential source of various bioactive substances. The chemical composition of propolis depends on several factors, such as the different types of plant sources collected by bees, geographic origin, and the time of year in which they are produced, but it is known that pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 105 publications
0
36
0
1
Order By: Relevance
“…The brown propolis used in this study was collected in Brazil's southeastern region, where the Atlantic forest biome predominates [37] . The southeastern Brazilian region is the leading producer of green propolis type, its botanical source B. dracunculifolia is characterized by flavonoids and prenylated phenolic compounds such as artepillin C, drupanin, and baccharin [28] . These compounds were not found in this brown propolis, revealing that B. dracunculifolia does not participate in its composition.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The brown propolis used in this study was collected in Brazil's southeastern region, where the Atlantic forest biome predominates [37] . The southeastern Brazilian region is the leading producer of green propolis type, its botanical source B. dracunculifolia is characterized by flavonoids and prenylated phenolic compounds such as artepillin C, drupanin, and baccharin [28] . These compounds were not found in this brown propolis, revealing that B. dracunculifolia does not participate in its composition.…”
Section: Resultsmentioning
confidence: 92%
“…Some of the isolated phenolic compounds are common to other types of propolis. Ferulic acid and caffeic acid are found in brown, green, and red types of Brazilian propolis [6,28] . The other phenolic compounds were identified in many different types of propolis over the world.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported for the first time 15,16-epoxy-19-hydroxy-1,3,13(16),14-clerodatetraen-18-oic acid (terpens class), and E-baccharin 5"-aldehyde (phenolic compound) in both green Brazilian propolis and B. dracunculifolia leaves. Moreover, a comprehensive review on artepillin C, a diprenyl-p-hydroxycinnamic acid derivative, responsible for gastroprotective, anti-inflammatory, antimicrobial, antioxidant, and antitumor propolis effect was made recently [52].…”
Section: Main Classes Of Compoundsmentioning
confidence: 99%
“…Artepillin C has been extensively studied using cell culture and animal models rather than clinical studies. Indeed, artepillin C has been shown to have anti‐inflammatory, anti‐oxidant, antimicrobial and immunomodulatory properties in both in vitro and in vivo studies 27 . In many in vitro studies, artepillin C concentrations greater than 25 μmol L −1 have been shown to function as anti‐inflammatory and anti‐oxidant agents 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, artepillin C has been shown to have anti‐inflammatory, anti‐oxidant, antimicrobial and immunomodulatory properties in both in vitro and in vivo studies 27 . In many in vitro studies, artepillin C concentrations greater than 25 μmol L −1 have been shown to function as anti‐inflammatory and anti‐oxidant agents 27 . In a rat model, artepillin C levels in blood withdrawn from the portal vein and abdominal artery were measured after the administration of artepillin C by gastric intubation 28 .…”
Section: Discussionmentioning
confidence: 99%